Аналіз досліджень впливу взуття на розподіл навантаження у стопі - Голяк, О. Д.; Носова, Я. В. (My University, 2025)
This study analyzes modern research on the effects of barefoot and orthopedic footwear on plantar load distribution. The advantages and limitations of two major diagnostic methods – pedobarography and computerized plantography – are compared. Pedobarography provides high-precision quantitative data in static and dynamic conditions, including peak pressure, contact area, and center-of-pressure trajectory, making it the most informative tool for biomechanical assessment. In contrast, computerized plantography, despite enhanced digital processing, delivers mainly morphometric information and does not measure real pressure values. More than 20 scientific sources were reviewed, identifying the most frequently analyzed parameters: Peak Pressure, Pressure–Time Integral, and contact area. The review highlights the lack of standardized measurement protocols and insufficient long-term studies evaluating foot adaptation to orthopedic footwear. The need for a unified methodology to compare the effects of barefoot and orthopedic footwear on plantar load distribution is emphasized, as well as the necessity for national research with representative samples.
Keywords: педобарографія; стопа; плантографія; біомеханіка ходи